2022
DOI: 10.3389/fmicb.2021.822749
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bivalent Live Vectored Vaccine Against Classical Swine Fever and HP-PRRS Revealed Adequate Heterogeneous Protection Against NADC30-Like Strain

Abstract: The recombinant bivalent live vectored vaccine rPRRSV-E2 has been proved to be a favorable genetic engineering vaccine against classical swine fever (CSF) and highly pathogenic porcine reproductive and respiratory syndrome (HP-PRRS). NADC30-like strains have recently emerged in China and caused severe disease, and it is necessary to evaluate the vaccine candidate for the currently circulating viruses. This study established a good challenge model to evaluate the candidate rPRRSV-E2 vaccine in preventing infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…According to the results of this study and previous studies, QYYZ-like strains have been occasionally reported in northern China ( 19 , 26 , 28 , 53 ) but are mainly prevalent in southern and central China ( 12 – 16 , 23 – 25 , 27 , 29 , 30 , 32 ). Although recombination of PRRSV is very common, many non-recombination strains of JXA1-like ( 54 ), VR2332-like ( 28 ) and NADC30-like/NADC34-like PRRSV ( 7 , 55 ) have been reported after long-term evolution in China. All QYYZ-like strains were recombined with other lineages of PRRSV except the prototype strain QYYZ.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of this study and previous studies, QYYZ-like strains have been occasionally reported in northern China ( 19 , 26 , 28 , 53 ) but are mainly prevalent in southern and central China ( 12 – 16 , 23 – 25 , 27 , 29 , 30 , 32 ). Although recombination of PRRSV is very common, many non-recombination strains of JXA1-like ( 54 ), VR2332-like ( 28 ) and NADC30-like/NADC34-like PRRSV ( 7 , 55 ) have been reported after long-term evolution in China. All QYYZ-like strains were recombined with other lineages of PRRSV except the prototype strain QYYZ.…”
Section: Resultsmentioning
confidence: 99%
“…This PRRSV originated in the United States and has become one of the major endemic strains in China since 2016 [ 57 ]. The pathogenicity of NADC30-like PRRSVs ranges from moderate [ 26 , 36 , 38 ] to high [ 32 , 33 , 58 ], and most of them are moderately pathogenic [ 26 , 36 , 37 , 38 , 39 , 40 , 41 , 44 , 47 , 48 , 53 ]; however, the current commercial vaccines, Ingelvac PRRS MLV/RespPRRS MLV [ 44 , 52 ], CH-1a [ 47 ], HuN4-F112 [ 51 ], JXA1-P80 [ 52 ], R98 [ 53 ], TJM-F92 [ 51 ], and GDr180 [ 26 , 51 ], do not provide completely effective protection against NADC30-like PRRSVs. Here, we selected the moderately pathogenic NADC30-like PRRSV SD strain and described a newly developed lineage 1 PRRSV vaccine candidate, SD-R, which is efficacious in the prevention of clinical infection caused by NADC30-like PRRSVs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PRRSV vaccines have poor cross-protection effects [ 45 , 51 ]. Most studies have found that MLV cannot provide complete cross-protection in NADC30-like infected piglets, including shortening the period of fever with fewer pig numbers of clinical manifestations [ 37 , 44 , 47 , 51 , 52 , 53 ], only improving body weight gain at some point in the study [ 37 , 44 , 48 , 52 ], without decreasing the viremia or viral loads in tissues [ 51 , 64 ], and pathological lesions in lung and lymphoid tissues [ 37 , 47 , 51 , 52 ]; however, surprisingly, SD-R could provide better cross-protection (including no fever, a significant improvement in weight gain, a significantly reduced viral load in blood and tissues, and no visible pathological damage) ( Table S2 ), even though the genomic nucleotide similarity of SD and HLJWK108-1711 was only 89.9%. All the piglets immunized with SD-R and then challenged with SD or HLJWK108-1711 survived without any major clinical signs at any point in the experimental period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2013, the NADC30-like PRRSV that likely originated from the NADC30 PRRSV strain circulating in North America around 2008, has been isolated and widely spread in China ( Zhao et al., 2015 ; Zhou et al., 2015 ; Wang et al., 2017 ). Although the pathogenicity of NADC30-like PRRSV is lower than that of HP-PRRSV, NADC30-like PRRSV has high variability and is prone to recombination with other PRRSV to form new PRRSV strains with complex genetic backgrounds and genomic characteristics ( Zhang et al., 2016 ; Zhou et al., 2018 ; Chen P. et al, 2021 ; Guo et al., 2021 ; Li Y. et al., 2021 ). Currently, NADC30-like PRRSV and HP-PRRSV are the dominant strains in China ( Li et al., 2016 ; Guo et al., 2019 ; Li L. et al, 2021 ; Zhang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%